2020
DOI: 10.2196/18653
|View full text |Cite
|
Sign up to set email alerts
|

Engagement, Acceptability, Usability, and Preliminary Efficacy of a Self-Monitoring Mobile Health Intervention to Reduce Sedentary Behavior in Belgian Older Adults: Mixed Methods Study

Abstract: Background Although healthy aging can be stimulated by the reduction of sedentary behavior, few interventions are available for older adults. Previous studies suggest that self-monitoring might be a promising behavior change technique to reduce older adults’ sedentary behavior. However, little is known about older adults’ experiences with a self-monitoring–based intervention aimed at the reduction of sedentary behavior. Objective The aim of this study i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 36 publications
2
38
1
Order By: Relevance
“…This study reports on part of a larger mixed methods study being conducted to evaluate a self-monitoring mHealth intervention to reduce sedentary behavior in older adults [16]. The study was registered at ClinicalTrials.gov (identification number: NCT04003324) and was approved by the Committee of Medical Ethics of the Ghent University Hospital (Belgian registration number 2019/0398).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study reports on part of a larger mixed methods study being conducted to evaluate a self-monitoring mHealth intervention to reduce sedentary behavior in older adults [16]. The study was registered at ClinicalTrials.gov (identification number: NCT04003324) and was approved by the Committee of Medical Ethics of the Ghent University Hospital (Belgian registration number 2019/0398).…”
Section: Methodsmentioning
confidence: 99%
“…To be eligible for the current study, participants needed to (1) be at least 60 years old, (2) be Dutch-speaking, (3) be able to walk 100 meters without severe difficulties, and (4) have a smartphone. A detailed description of the study procedure has been published elsewhere [16]. Briefly, baseline data, including sociodemographic characteristics, were collected before the start of the intervention.…”
Section: Participants Procedure and Interventionmentioning
confidence: 99%
“…While many rapid pathogen detection technologies have undergone validity analyses, there is a literature gap of usability analyses for such technologies [14][15][16][17][18]. Many usability studies instead evaluate technologies that aid interventions such as behavioral change, treatment adherence, or clinical decision making [23][24][25][26]. Thus, this study can serve as a model of iterative convergent mixed methods research design for device development to further promote usability analysis of rapid pathogen detection technologies and produce rapid detection devices that better fit into user workflows for increased uptake.…”
Section: Principal Findingsmentioning
confidence: 99%
“…While the field of mHealth and rapid diagnostic testing for infectious disease is fast-growing, few rapid pathogen detection technologies have been developed for environmental surveillance [12,22]. Moreover, many mHealth usability studies have evaluated interventions such as behavioral change, medication adherence, or clinical decision-making technologies, but there is a literature gap for usability studies evaluating rapid pathogen detection technology [23][24][25][26]. By providing input in the device development process, end users can become cocreators and feel ownership in the device design, enabling greater uptake and integration into workflows.…”
Section: Introductionmentioning
confidence: 99%
“…Older adults have had high levels of engagement with mHealth interventions and, in one study, have demonstrated higher levels of engagement with digital diabetes self-management than their younger counterparts. 23 , 24 Despite these promising studies, there is still a lack of research on longitudinal engagement with self-management technologies by those with multiple chronic conditions, with a view to understanding how best to facilitate and promote sustained engagement to maximise benefits.…”
Section: Introductionmentioning
confidence: 99%